Photobiomodulation Response From 660 nm is Different and More Durable Than That From 980 nm. Issue 9 (16th May 2021) - Fuchs, Christiane; Schenk, Merle Sophie; Pham, Linh; Cui, Lian; Anderson, Richard Rox; Tam, Joshua
Abstract : Background and Objectives: Photobiomodulation (PBM) therapy uses light at various wavelengths to stimulate wound healing, grow hair, relieve pain, and more—but there is no consensus about optimal wavelengths or dosimetry. PBM therapy works through putative, wavelength‐dependent mechanisms including direct stimulation of mitochondrial respiration, and/or activation of transmembrane signaling channels by changes in water activity. A common wavelength used in the visible red spectrum is ~660 nm, whereas recently ~980 nm is being explored and both have been proposed to work via different mechanisms. We aimed to gain more insight into identifying treatment parameters and the putative mechanisms involved. Study Design/Materials and Methods: Fluence‐response curves were measured in cultured keratinocytes and fibroblasts exposed to 660 or 980 nm from LED sources. Metabolic activity was assessed using the MTT assay for reductases. ATP production, a major event triggered by PBM therapy, was assessed using a luminescence assay. To measure the role of mitochondria, we used an ELISA to measure COX‐1 and SDH‐A protein levels. The respective contributions of cytochrome c oxidase and ATP synthase to the PBM effects were gauged using specific inhibitors. Results: Keratinocytes and fibroblasts responded differently to exposures at 660 nm (red) and 980 nm (NIR). Although 980 nm required much lower fluence for cell stimulation, the resulting increase in ATP levels was short‐term, whereas 660 nm stimulation elevated ATP levels for at least 24 hours. COX‐1 protein levels were increased following 660 nm treatment but were unaffected by 980 nm. In fibroblasts, SDH‐A levels were affected by both wavelengths, whereas in keratinocytes only 660 nm light impacted SDH‐A levels. Inhibition of ATP synthase nearly completely abolished the effects of both wavelengths on ATP synthesis. Interestingly, inhibiting cytochrome c oxidase did not prevent the rise in ATP levels in response to PBM treatment. Conclusion: To the best of our knowledge, this is the first demonstration of differing kinetics in response to PBM therapy at red versus NIR wavelength. We also found cell‐type‐specific differences in PBM therapy response to the two wavelengths studied. These findings confirm that different response pathways are involved after 660 and 980 nm exposures and suggest that 660 nm causes a more durable response. © 2021 Wiley Periodicals LLC.